WEBSITES AS SCIENCE LEARNING ON INVERTEBRATE ANIMALS MATERIALS AT STATE JUNIOR HIGH SCHOOL 1 TEGALDLIMO BANYUWANGI - Etika Rosyida; Rafiatul Hasanah (INSECTA: Integrative Science Education and Teaching Activity Journal, 2021)
This study aims  to determine the validity of the development of website-based science learning media on invertebrate animal material for grade 7 in Junior High School, and to determine student responses to the development of website-based science learning media on invertebrate animal material. This research was a type of R&D (Research and Development) research which refers to the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development research model of Robert Maribe Branch. The data collection instruments in this study were validation questionnaires and student response questionnaires. Validation was carried out by material experts, media experts, and science teachers. The development trial to determine student responses to the developed product was carried out in two stages, namely a small-scale trial consisting of 6 students and a large-scale trial consisting of 32 students. Based on the results of validation from experts on website-based science learning media, it showed that the assessment of material experts was 96.16%, media expert assessments was 89.12% and assessments from science teachers was 89.83% . In this case, the average percentage of the expert's assessment was 91.70%, which means it was included in the "Very Valid" category and tested on students, and Small-scale trials obtained an average percentage of 94.28%. Then continued large-scale trials and obtained an average percentage of 92.00%. which means “Very Interesting”.